Noise-induced cochlear neuropathy is selective for fibers with low spontaneous rates - Furman, Adam C.; Kujawa, Sharon G.; Liberman, M. Charles (Journal of neurophysiology, 2013)
Acoustic overexposure can cause a permanent loss of auditory nerve fibers without destroying cochlear sensory cells, despite complete recovery of cochlear thresholds ( Kujawa and Liberman 2009 ), as measured by gross neural potentials such as the auditory brainstem response (ABR). To address this nominal paradox, we recorded responses from single auditory nerve fibers in guinea pigs exposed to this type of neuropathic noise (4- to 8-kHz octave band at 106 dB SPL for 2 h). Two weeks postexposure, ABR thresholds had recovered to normal, while suprathreshold ABR amplitudes were reduced. Both thresholds and amplitudes of distortion-product otoacoustic emissions fully recovered, suggesting recovery of hair cell function. Loss of up to 30% of auditory-nerve synapses on inner hair cells was confirmed by confocal analysis of the cochlear sensory epithelium immunostained for pre- and postsynaptic markers. In single fiber recordings, at 2 wk postexposure, frequency tuning, dynamic range, postonset adaptation, first-spike latency and its variance, and other basic properties of auditory nerve response were all completely normal in the remaining fibers. The only physiological abnormality was a change in population statistics suggesting a selective loss of fibers with low- and medium-spontaneous rates. Selective loss of these high-threshold fibers would explain how ABR thresholds can recover despite such significant noise-induced neuropathy. A selective loss of high-threshold fibers may contribute to the problems of hearing in noisy environments that characterize the aging auditory system.